2021
DOI: 10.3390/su13063137
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Precast Concrete Using Food Industry-Filtered Recycled Diatoms

Abstract: The concrete industry is under increasing pressure to reduce greenhouse gas emissions. An immediate solution is to minimize the amount of Portland cement used by partially substituting other supplementary cementitious materials. This article presents the results of an experimental campaign on the influence of replacing Portland cement with both calcined and uncalcined diatomites from the filtration of beer and wine in the production of elements made of vibro-pressed pre-cast concrete, such as pipes. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Numerous studies and experiments have focused on the use of sustainable raw materials, particularly the valorization and reuse of waste materials in the production of mortars and cements. This approach aims to optimize the properties of construction materials, especially mechanical and thermal ones, while reducing the extraction and use of raw materials and minimizing landfill waste disposal [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In various studies, waste products, such as fly ash (FA) [28,32], plastic waste [33], green pozzolan (GP) [34], waste paper sludge ash (WPSA) [35], food waste [36,40], and wood biomass ash (WBA-wood bottom ash) from power plants [38,39] have been added to concrete or mortar mixes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies and experiments have focused on the use of sustainable raw materials, particularly the valorization and reuse of waste materials in the production of mortars and cements. This approach aims to optimize the properties of construction materials, especially mechanical and thermal ones, while reducing the extraction and use of raw materials and minimizing landfill waste disposal [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In various studies, waste products, such as fly ash (FA) [28,32], plastic waste [33], green pozzolan (GP) [34], waste paper sludge ash (WPSA) [35], food waste [36,40], and wood biomass ash (WBA-wood bottom ash) from power plants [38,39] have been added to concrete or mortar mixes.…”
Section: Introductionmentioning
confidence: 99%
“…This approach aims to optimize the properties of construction materials, especially mechanical and thermal ones, while reducing the extraction and use of raw materials and minimizing landfill waste disposal [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In various studies, waste products, such as fly ash (FA) [28,32], plastic waste [33], green pozzolan (GP) [34], waste paper sludge ash (WPSA) [35], food waste [36,40], and wood biomass ash (WBA-wood bottom ash) from power plants [38,39] have been added to concrete or mortar mixes. The use of EPS and recycled expanded polystyrene (R-EPS), as a replacement for aggregate in concrete and mortar formulations, has been extensively experimented with, successfully achieving lightweight and thermally efficient mortars.…”
Section: Introductionmentioning
confidence: 99%
“…The low cost, abundance, easy availability, excellent biocompatibility, non-toxicity, thermal stability, and chemical inertness make diatomite an intriguing material for applications ranging from filtration to pharmaceutics [ 27 , 28 ]. The unique combination of physical and chemical properties of diatomite makes it applicable for several industrial uses, as a filtration media for chemicals, various beverages, drinking water, sugar, etc., without altering their natural properties or for the removal of inorganic and organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Sardemir et al [ 20 ] found that the incorporation of diatomite by mixing calcined diatomite into cement mortar could effectively improve the strength of mortar, and 15% was the optimal dosage. Rodriguez et al [ 21 ] studied the compressive strength and resistance of diatomite-added concrete to chloride ion erosion. After the addition of diatomite, the porosity and pore size decreased, the strength increased by 15%, and the resistance to chloride ion erosion increased by 5% after 90 days.…”
Section: Introductionmentioning
confidence: 99%